2020
DOI: 10.3390/diagnostics10060370
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes between Idiopathic Frozen Shoulder and Diabetic Frozen Shoulder After a Single Ultrasound-Guided Intra-Articular Corticosteroid Injection

Abstract: There is no consensus on the use of intra-articular corticosteroid injections in diabetic frozen shoulder (FS). Thus, we aimed to compare clinical outcomes after intra-articular corticosteroid injections in patients with diabetic FS and idiopathic FS. Data collected from 142 FS patients who received glenohumeral joint intra-articular corticosteroid injections were retrospectively reviewed. Thirty-two patients were diagnosed with diabetic FS and 110 patients with idiopathic FS. Data including visual analog scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Corticosteroid injection was first introduced since the 1950 second [ 39 ] and has frequently been used in tendinous lesions. [ 10 , 40 ] A number of clinic trials have revealed the short-term effects of corticosteroid injection for the treatment of rotator cuff lesions, [ 41 , 42 ] however, no reliable evidence for its long-term effects. Recently published systematic reviews have shown that corticosteroid injection is superior to PRP injection in treatment of elbow epicondylitis [ 29 , 43 ] and hip osteoarthritis [ 44 ] in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid injection was first introduced since the 1950 second [ 39 ] and has frequently been used in tendinous lesions. [ 10 , 40 ] A number of clinic trials have revealed the short-term effects of corticosteroid injection for the treatment of rotator cuff lesions, [ 41 , 42 ] however, no reliable evidence for its long-term effects. Recently published systematic reviews have shown that corticosteroid injection is superior to PRP injection in treatment of elbow epicondylitis [ 29 , 43 ] and hip osteoarthritis [ 44 ] in the short-term.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the treatment of FS is more difficult in patients with than without diabetes, and patients with diabetes show a more diminished response to treatment. [37][38][39][40] Diabetic patients commonly have more limitations of pROM than non-diabetic patients. 41 High blood glucose levels cause excessive glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Those with predisposing metabolic disease such as diabetes mellitus or with a primary pathology in the shoulder prior to the development of adhesive capsulitis are considered to have secondary frozen shoulder. 6 , 7 Tertiary frozen shoulder arises as a grave complication of fracture treatment in the shoulder girdle or rotator cuff repair and may occur despite early rehabilitation.…”
Section: Introductionmentioning
confidence: 99%